PENGGUNAAN BAHASA INDONESIA DALAM KARYA ILMIAH GURU SMP DI KABUPATEN PIDIE JAYA - Rahmi, Hayatun; S, Nofiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
This research is entitled The Use of Indonesian in Scientific Work of Middle School Teachers in Pidie Jaya Regency. The formulation of the problem in this study is